Splenic Artery Embolization for Upper Gastrointestinal Bleeding Caused by Hemosuccus Pancreaticus - Evghenii Gutu; Dumitru Casian; Roman Smolnitchi; Vasile Culiuc; Andrei Scureac (Case Reports in Gastrointestinal Medicine)
Hemosuccus pancreaticus (HP) is a rare but potentially life-threatening condition, characterized by upper gastrointestinal bleeding from the ampulla of Vater, often originating from a ruptured pseudoaneurysm of the peripancreatic arteries. Despite its rarity, HP presents a diagnostic and therapeutic challenge due to its elusive clinical presentation and complex underlying pathophysiology. In this case report, we presented a compelling instance of HP, diagnosed in a 48-year-old man, complicated with gastrointestinal bleeding and severe anemia successfully managed with urgent endovascular intervention. We highlighted the importance of early recognition, prompt intervention, and interdisciplinary collaboration in achieving favorable outcomes in patients afflicted by this distinctly unusual condition.